Composition Portfolio - Hanmer, Paul Dylan (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Extract from Introduction: "In the cover bands I worked with, I used to do what all my colleagues in these bands were doing to learn and remember repertoire; transcribe "by ear" and then rehearse with the whole band. Later, when I joined "909" [a cover band named after the "909" model of drum-box developed and built by the Japanese company, Roland] I learned to extend that skill by notating my transcriptions and then playing from these self-made keyboard parts. All the instrumentalists in that band likewise played from their own notated transcriptions and, from that time onward it became rarer for me to do any kind of performance work without a set of self-made parts to read from or refer to. I had thus reverted to performing from musical notation. Even later, when I became involved almost exclusively in improvisational music performance, I never quite abandoned the notion of having notated keyboard or piano parts to hand, as a reference or guide. Since about 1990, I have led a life that has increasingly left pop music behind and instead embraced working with improvising musicians; those who wish to explore South African folk idioms in their compositional and performance output, as well as others who have a deep love of jazz music. At the same time, I have re-entered the realm of classical music and music-making; often through writing arrangements of my own music, which would incorporate classically trained players, as well as in response to commissions to compose [for particular musicians or groups of musicians] fully notated pieces of music "“ such as the works in this PhD portfolio. Yet, there are many circumstantial factors that feed into my composing, and exert an influence on my creativity. A major step in this particular direction came during 2002 when composer, Michael Blake, asked me to contribute to The Bow Project. This commission brought me into close contact with the [then intact and very active] Sontonga Quartet. Several further requests for, and commissions of, new works followed on from there. Two such works constitute the major portion of the portfolio to which these reflexive commentaries refer."
Keywords: Composition (Music); String quartets Scores; Symphonies Scores; Music -- South Africa